Catheter Ablation in Complex Atrial Arrhythmias: Pilot Study Evaluating a 3D Wide-Band Dielectric Imaging System - Pongratz, Janis; Dorwarth, Uwe; Riess, Lukas; Schwartz, Yitzhack; Wankerl, Michael; Hoffmann, Ellen; Straube, Florian (Frontiers in Cardiovascular Medicine, 2022)
Background Cryoballoon ablation (CBA) for pulmonary vein isolation (PVI) is a standard in atrial fibrillation (AF) ablation but might not be enough in complex atrial arrhythmias (AA). An open three-dimensional wide-band dielectric imaging system (3D-WBDIS) has been introduced to guide CBA. Material and Methods Pilot study evaluating feasibility and safety of 3D-WBDIS in combination with CBA and optional radiofrequency ablation (RFA) in patients with complex AA defined as (1) history of persistent AF, (2) additional atrial tachycardia/flutter, or (3) previous left atrial ablation. Results Prospectively, seventeen patients, 68.9 ± 12.2 years of age, with complex AA were enrolled. In 70 pulmonary veins (PV), balloon positioning maneuvers (n = 129) were guided additionally by the occlusion tool (1.84/PV). Compared to angiography, its sensitivity and specificity was 94.5, and 85%, respectively. CBA-PVI was achieved in 100% of PVs including variants. In 68 maps, the median number of mapping points was 251.0 (interquartile range (IQR) 298.0) with a median map volume of 52.8 (IQR 83.9) mL. Following CBA, six additional arrhythmias (two right and two left atrial flutter, one left atrial appendage tachycardia, and one atrioventricular nodal reentry tachycardia) were identified and successfully ablated by means of RFA in five patients (29.4%). Left atrial and fluoroscopy times were 88 (IQR 40) and 20 (IQR 10) minutes, respectively. Dose area product was 1,100 (IQR 1252) cGyxcm2. Freedom from AA after 6 months follow-up time and 90 days blanking period was documented in 10/17 (59%) patients, and 8/17 (47%) without a blanking period. No major complication was observed. Conclusion The combined use of CBA with optional RFA guided by a novel 3D-WBDIS is feasible and safe in patients suffering from complex AA. The occlusion tool shows high sensitivity and specificity for assessment of the balloon occlusion. Additional arrhythmias were successfully mapped and ablated. Short-term outcome is promising, and subsequent prospective, larger outcome studies are necessary to confirm our observations.